MUCIN PROFILE OF PROSTATIC LESIONS: A HISTOCHEMICAL APPROACH FOR DIFFERENTIATION IN A TERTIARY CARE CENTER. - Dr. Srikanth.K; Raj, Dr. Vijay David; Suresh, Dr. Natarajan; Vimal, Dr. Mourouguessine (Student’s Journal of Health Research Africa, 2025)
Background: Microscopic differentiation of benign and low grade malignant lesions of prostate pose a challenging task for the pathologists. Immunohistochemistry markers can prove costlier in resource poor settings. Objectives : To assess the utility of mucin stains in evaluating and differentiating benign and malignant lesions of prostate. Materials and Methods : 100 prostatic biopsies received in the Pathology department of atertiary care hospital over a period of one and half years were included in this study. In additiontoroutineH&E,thesectionswerestainedwithPeriodicacidSchiff (PAS),Alcianblue(AB) andMucicarmine(MC) stains. Results: Out of 100 prostatic biopsies studied, 90% of benign cases and 53% malignant lesions showed positivity with Periodic acid Schiff (PAS) stain. With Alcian blue, 67% of malignant lesions showed positivity and with Mucicarmine 60% of malignant lesions showed positivity. In contrast only 1% of benign lesions were positive with Alcian blue and Mucicarmine Conclusions: Neutral mucin was found to be more frequently positive in benign lesions of prostate whereas acidic mucin is expressed only in malignant lesions